The combined effect of time of day and menstrual cycle on lactate threshold - Forsyth, J. J.; Reilly, T. (Medicine & Science in Sports & Exercise, 2005)
Purpose: This study examined the isolated and combined effects of time of day and menstrual cycle phase on the determination of the lactate threshold (Tlac) and blood lactate concentration.